Characteristics and management of stroke in Korea: 2014–2018 data from Korean Stroke Registry. Issue 6 (August 2020) - Jeong, Han-Yeong; Jung, Keun-Hwa; Mo, Heejung; Lee, Chan-Hyuk; Kim, Tae Jung; Park, Jong-Moo; Oh, MiSun; Lee, Ji Sung; Kim, Beom Joon; Kim, Joon-Tae; Kim, Jinkwon; Seo, Woo-Keun; et al.
Background: Lifestyle changes and evolving healthcare practices in Korea have influenced disease patterns and medical care. Since strokes have high disease burden in countries with aging populations, it is necessary to evaluate the associated recent disease characteristics and patient care patterns. The Korean Stroke Registry is a nationwide, multicenter, prospective, hospital-based stroke registry in Korea used to monitor these changes across the population. Aims: We aimed to evaluate the recent status of clinical characteristics and management of stroke cases in order to identify changes in the Korean population across time. Methods: This study used Korean Stroke Registry data from patients experiencing ischemic stroke or transient ischemic attack patients, between 2014 and 2018. We analyzed data on demographics, risk factors, stroke subtypes, and treatments that included thrombolysis. Results: A total of 39, 291 patients (mean age 68.0 ± 13.0, 58.3% male) were analyzed. The proportions of hypertension, diabetes mellitus, dyslipidemia, atrial fibrillation, and prior stroke were 63.4%, 30.9%, 27.7%, 19.4%, and 17.1%, respectively. In the stroke subtype analysis, the frequency of large artery atherosclerosis was highest (32.6%), followed by cardioembolism (21.3%) and small vessel occlusion (19.9%). Acute reperfusion therapy was conducted in 15.3% of cases (11.7% using intravenous tPA and 7.3% using intra-arterial thrombectomy). Intra-arterial thrombectomy also demonstrated a steep increasing trend over time (RR 1.095 (1.060–1.131), p  < 0.001). Conclusions: This study provided analysis of nationwide, hospital-based, quality-controlled data from the Korean Stroke Registry database regarding changes in the characteristics, risk factors, and treatments of strokes in Korea.